A Comprehensive Review on the Nutritional and Medicinal Significance of Kushmanda or Ash Gourd as per Ayurveda - Nimmy V S (International Journal of Ayurveda and Pharma Research, 2022)
Ayurveda stresses on the use of herbs as both food and medicine based on their nutritional and medicinal values respectively. While the Rasa (taste) of the medicinal plant determines its dietary value, the Veerya (potency) bestows its therapeutic actions. Kushmanda or Ash gourd (Benincasa hispida (Thunb.) Cogn.) is such a fruit appraised in Ayurveda for both its medicinal and nutritive values. It is of utmost importance to showcase the properties and actions of this indigenous herb as it is easily available, safe and affordable to the common people. Kushmanda is used in managing ulcers, epilepsy, urinary disorders and in treating poisoning. The seeds and fruit juice of Kushmanda is claimed to be nootropic (Medhya) and is recommended in Ayurveda for enhancing memory and other cognitive functions. Experimental studies prove that Kushmanda possesses multitude of actions including anti-diabetic, anti-inflammatory, antioxidant, hypolipidemics, hypoglycaemic etc. A thorough review shows that the presence of phenols, triterpenes, sterols, and glycosides of ash gourd makes it useful for treatment of ulcers, inflammation, epilepsy and other nervous disorders. Further elaborate clinical studies need to be undertaken to explore and strengthen the claims on efficacy of Benincasa hispida (Thunb.) Cogn. in nervous disorders, ulcers and diabetes.